Improving the Performance of Lithium-Ion Batteries by Using Spinel Nanoparticles. (6th April 2008) - Arrebola, J. C.; Caballero, A.; Hernán, L.; Morales, J.
Abstract : In this work, we examined the use of nanospinels to construct batttery electrodes. We chose two spinels suitable as cathode materials (LiMn 2 O 4 andLiNi 0.5 Mn 1.5 O 4, which are representative of 4 and 5 V versus Li metal, resp.) and one providing good results as anode (Li 4 Ti 5 O 12 ). In order to ensure good cell performance, nanometric particles must meet another requirement; thus they should contain few surface or bulk defects (i.e., they should be highly crystalline). Because the synthesis of such spinels usually requires a thermal treatment, ensuring that they will meet both requirements entails accuratly controlling in the synthesis conditions. Thermal decomposition of nanooxalate in the spinel-conaining elements obtained by mechanochenical activation in the presence of polymers provides a simple, effective route for this purpose. We prepared two types of hybrid lithium-ion batteries usingLiMn 2 O 4 andLiNi 0.5 Mn 1.5 O 4 as cathode materials, andLi 4 Ti 5 O 12 as anode material. The electrochemical properties of these cells were compared with those of a similar configuration made from micrometric particles. The nano-nano configuration exhibited higher reversibility and better performance than the micro-micro configuartion in both types of cells, possibly as a result of lithium ions in the former being able to migrate more easily into the electrode material.